A Literature Review of Findings in Physical and Emotional Abuse in Elderly - Vidya, Bhagat; Kyin, Htwe (2018)
Physical and emotional abuse is ongoing problem that go with public health concern. Physical injuries and emotional distress in elder is become social hubbubs that needs medical attention. Current study aims at eliciting patterns that will aid in detection of these social malaises. This review study was completed using electronic databases that had analyzed reviewing 100 articles. This review study used articles from 1985 to 2015 that was suitable for tracking reviews that gives information on physical and emotional abuse in elderly from case-control studies, cross-sectional studies, and case series or in medico legal reports were. A review of 63 articles from a total of 100 articles screened draw together different aspects of the physical abuse and emotional abuse. Study concluded that frequency of physical and psychological elder abuse is seen with less difference it’s also determines the fact commonality of multiple abuse, its impact and prevention. Implication of this review study opens the door to come out with different intervention against this social malaise.